FREQUENCY OF LEFT ATRIAL AND APPENDAGE CLOT IN PATIENTS WITH SEVERE MITRAL STENOSIS - Hassan, Mahmood ul; Hussain, Cheragh; Gul, Adnan Mahmood; Jan, Hikmat ullah; Hafizullah, Mohammad (Journal of Ayub Medical College Abbottabad, 2010)
Background: Left atrial thrombus is common in patients with mitral stenosis and atrial fibrillation; but how frequent it is in our population? The objective of study was to see the frequency of left atrial and appendage clot on trans-oesophageal echocardiography in symptomatic patients with severe mitral stenosis planned for PTMC. Methods: Trans-oesophageal echocardiographic data retrieved from computer database Cardiology department, Lady Reading Hospital, Peshawar from August 1998 to Mach 2008. Patients admitted for PTMC under went trans-oesophageal echocardiography for detection of left atrial and appendage clot and quantification of mitral regurgitation. Data was analyzed on SPSS. Results: Out of 1544 patients, males were 608 (39.4%), females were 936 (60.6%). Mean age was 30.84±12.6. Mean age of males was 30.56±13.1 years and females were 31.02±12.6 years. Minimum age was 8 years and maximum was 76 years. The mean LA size was 43.82±2.12mm.Atrial fibrillation was observed in 289 (18.7%).Overall clot was seen in 224 (14.5%) patients. Left atrial appendage clot seen in 202 (89.73%).LA clot seen in 9 (4.02%). LAA/LA clot seen in 14 (6.25%). No significant difference was observed for clot among the gender distribution (p=0.42). Significant correlation was observed for clot in patients with AF and LA size ‰¥45 mm, (p>0.001). Conclusion: The frequency of left atrial and appendage clots on trans-oesophageal echocardiography in patients with severe mitral stenosis is common and more frequent in patients with AF and LA size ‰¥45 mm. Keywords: LA, LAA, CLOT, TEE, PTMC